Mitochondrial DNA Markers Reveal High Genetic Diversity but Low Genetic Differentiation in the Black Fly Simulium tani Takaoka & Davies along an Elevational Gradient in Malaysia - Low, Van Lun; Adler, P.H.; Takaoka, Hiroyuki; Ya'cob, Z.; Lim, Phaik Eem; Tan, T.K.; Lim, Yvonne Ai Lian; Chen, Chee Dhang; Norma-Rashid, Y.; Sofian-Azirun, Mohd (Public Library of Science, 2014)
The population genetic structure of Simulium tani was inferred from mitochondria-encoded sequences of cytochrome c oxidase subunits I (COI) and II (COII) along an elevational gradient in Cameron Highlands, Malaysia. A statistical parsimony network of 71 individuals revealed 71 haplotypes in the COI gene and 43 haplotypes in the COII gene; the concatenated sequences of the COI and COII genes revealed 71 haplotypes. High levels of genetic diversity but low levels of genetic differentiation were observed among populations of S. tani at five elevations. The degree of genetic diversity, however, was not in accordance with an altitudinal gradient, and a Mantel test indicated that elevation did not have a limiting effect on gene flow. No ancestral haplotype of S. tani was found among the populations. Pupae with unique structural characters at the highest elevation showed a tendency to form their own haplotype cluster, as revealed by the COII gene. Tajima’s D, Fu’s Fs, and mismatch distribution tests revealed population expansion of S. tani in Cameron Highlands. A strong correlation was found between nucleotide diversity and the levels of dissolved oxygen in the streams where S. tani was collected.